Talahib Grass (Saccharum spontaneum. Linn.) a study of its potential as a source of natural dye. - Lachica, Maria Eloisa Santos
The experimental study aims to look into the possibility of extracting a natural dye from the leaves if the talahib grass. After conducting several research activities such as: (1) water extraction, (2) mordanting fabrics with alum at various concentrations (1%, 3% & 5%), (3) application of the extracted dye on natural fabrics (cotton, pina & silk) at various dye concentration (100%, 300% & 500%), and (4) subjected the dyed samples to light and wash fastness tests in the PTRI laboratory, it was found out that the leaves of the talahib grass, particularly the young fresh ones, could be a valuable source of natural dye. A yellow dye was extracted by boiling the leaves for an hour. Good affinity of the talahib dye to natural fibers, particularly on the dyed pina cloth was observed. However, with alum as a mordant, the good colorfastness to light and washing of the dye was not confirmed. Staining of the dyed fabrics on different undyed fibers was found negligible.